Impact of Aortoseptal Angle Abnormalities and Discrete Subaortic Stenosis on Left-Ventricular Outflow Tract Hemodynamics: Preliminary Computational Assessment - Shar, Jason A.; Brown, Kathleen N.; Keswani, Sundeep G.; Grande-Allen, Jane; Sucosky, Philippe (Frontiers in Bioengineering and Biotechnology, 2020)
Discrete subaortic stenosis (DSS) is an obstruction of the left ventricular outflow tract (LVOT) due to the formation of a fibromuscular membrane upstream of the aortic valve. DSS is a major risk factor for aortic regurgitation (AR), which often persists after surgical resection of the membrane. While the etiology of DSS and secondary AR is largely unknown, the frequent association between DSS and aortoseptal angle (AoSA) abnormalities has supported the emergence of a mechanobiological pathway by which hemodynamic stress alterations on the septal wall could trigger a biological cascade leading to fibrosis and membrane formation. The resulting LVOT flow disturbances could activate the valve endothelium and contribute to AR. In an effort to assess this hypothetical mechano-etiology, this study aimed at isolating computationally the effects of AoSA abnormalities on septal wall shear stress (WSS), and the impact of DSS on LVOT hemodynamics. Two-dimensional computational fluid dynamics models featuring a normal AoSA (N-LV), a steep AoSA (S-LV), and a steep AoSA with a DSS lesion (DSS-LV) were designed to compute the flow in patient-specific left ventricles (LVs). Boundary conditions consisted of transient velocity profiles at the mitral inlet and aortic outlet, and patient-specific LV wall motion. The deformation of the DSS lesion was computed using a two-way fluid-structure interaction modeling strategy. Turbulence was accounted for via implementation of the k-omega turbulence model. While the N-LV and S-LV models generated similar LVOT flow characteristics, the DSS-LV model resulted in an asymmetric LVOT jet-like structure, subaortic stenotic conditions (up to 2.4-fold increase in peak velocity, 45% reduction in effective jet diameter vs. N-LV/S-LV), increased vorticity (2.8-fold increase) and turbulence (5- and 3-order-of-magnitude increase in turbulent kinetic energy and Reynolds shear stress, respectively). The steep AoSA subjected the septal wall to a 23% and 69% overload in temporal shear magnitude and gradient, respectively, without any substantial change in oscillatory shear index. This study reveals the existence of WSS overloads on septal wall regions prone to DSS lesion formation in steep LVOTs, and the development of highly-turbulent, stenotic and asymmetric flow in DSS LVOTs, which support a possible mechano-etiology for DSS and secondary AR.